Protective role of the curcumin derivative, FM0807, in regulating JAK2/STAT3 and TGF-β1/SMAD2/3 signaling pathways in glomerular mesangial cells and renal function in db/db mice - Nanwen Zhang; Duoduo Lin; Honglin Wang; Ningning Zheng; Weipeng Lai; Liangyi Li; Jianhua Xu; Xiaole Chen (Acta Materia Medica)
To determine the protective effects of FM0807 against diabetes-induced renal inflammation and fibrosis and the underlying mechanisms in vivo and in vitro . FM0807 was administered to db/db mice. Glomerular mesangial cells (HBZY-1) were cultured under high glucose conditions with or without FM0807. Gene and protein expression was assessed by quantitative real-time PCR, western blotting, and immunofluorescence. Mitochondrial reactive oxygen species were detected with MitoSOX Red. FM0807 markedly reduced blood glucose, glycosylated hemoglobin, triglycerides, and low-density lipoprotein-cholesterol levels and improved the liver organ index, the high-density lipoprotein-cholesterol level, and renal function, as evidenced by decreased 24-h urinary protein excretion and the creatinine and blood urea nitrogen levels. FM0807 ameliorated pathologic renal changes in diabetic mice (reduced glomerulosclerosis, diminished interstitial cellular inflammation, and less tubular luminal narrowing). Treatment with FM0807 also led to a significant reduction in the expression of inflammatory markers, including JAK2, STAT3, TNF-α, IL-1β, IL-6, TGF-β1, and Smad2/3, in addition to alterations in the expression of proteins associated with kidney injury. These data suggest that FM0807 alleviates diabetes-induced renal inflammation and fibrosis by modulating the JAK2/STAT3 and TGF-β1/SMAD2/3 signaling pathways.